Modification of Cardiovascular Drugs in Advanced Heart Failure: A Narrative Review - Martínez-Sellés, Manuel; Grodzicki, Tomasz (Frontiers in Cardiovascular Medicine, 2022)
Advanced heart failure (HF) is a complex entity with a clinical course difficult to predict. However, most patients have a poor prognosis. This document addresses the modification of cardiovascular drugs in patients with advanced HF that are not candidates to heart transplantation or ventricular assist device and are in need of palliative care. The adjustment of cardiovascular drugs is frequently needed in these patients. The shift in emphasis from life-prolonging to symptomatic treatments should be a progressive one. We establish a series of recommendations with the aim of adjusting drugs in these patients, in order to adapt treatment to the needs and wishes of each patient. This is frequently a difficult process for patients and professionals, as drug discontinuing needs to balance treatment benefit with the psychological adaption to having a terminal illness. We encourage the use of validated assessment tools to assess prognosis and to use this information to take clinical decisions regarding drug withdrawal and therapeutic changes. The golden rule is to stop drugs that are harmful or non-essential and to continue the ones that provide symptomatic improvement.